Fear of crime in the sanctuary: comparing American and Ghanaian university students’ fearfulness - Boateng, Francis D. (International journal of offender therapy and comparative criminology, 2018)
While much is known about fear of crime in the West, little is known about how fearfulness of crime develops in non-Western societies, especially among university students. Representing the first attempt to empirically compare levels of fear of crime between Ghanaian and U.S. college students, this article examined students’ levels of fear of crime on campus, and tested the applicability of two evolving models of fear of crime—the vulnerability and reassurance models—using comparative data. The general finding is that Ghanaian and U.S. college students differ in terms of their rates of fearfulness on campus. This significant difference adds to the already existing differences between the two countries.